Vasopressor is the Drug of Choice in the Management of Cardiac Arrest Occurring in Early Spinal Anesthesia - Alam, M Intakhab; Rahman, M Lutfar; Haque, M Ekramul; Jesmin, S (TAJ: Journal of Teachers Association, 2009)
In Rajshahi Medical College Hospital this experience was based on 8 patients who got high spinal block for intended surgery for Caesarian section. These patients were totally apnoeic, cyanosed and there was no recordable pulse or blood pressure. Cardiac massage and artificial ventilation with rapidly introduced E.T.T. were instituted and inotrope Ephedrine was given without recovery. But when adrenaline was given in diluted form, soon pulse, B.P. respiration and consciousness were regained. doi: 10.3329/taj.v21i1.3219 TAJ 2008; 21(1): 50-52